THE EFFECT OF THE MASTERY LEARNING MODEL ON THE STUDENTS’ LEARNING OUTCOMES AT CLASS V OF PUBLIC ELEMENTARY SCHOOL 097795 PERASMIAN - Marta S.R Silaban; Patri Janson Silaban; Anton Sitepu (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper discusses the effect of applying the mastery learning model on students’ learning outcomes on the theme of our friendly environment at class V of SD Negeri 097795 Perasmian in the academic year 2022/2023. The research uses quantitative methods. The research population is 132 entire students at class I-VI of SD Negeri 097795 Perasmian. The sampling technique uses a purposive sample and the sample used is 39 students at class V. The research results indicate that students’ learning outcomes applying the mastery learning model are included in the excellent category level with an average of 80.5 with a correlation test result of 0.951, which means rcount (0.951) ≥ rtable (0.361), then Ha is accepted. Thus, there is an intense effect of applying the mastery learning model on students’ learning outcomes on the theme of our friendly environment at class V of SD Negeri 097795 Perasmian. It can be seen from the T-test results where tcount 2,665 ≥ ttable 2,048, hence Ha is accepted. It implies that there is a significant positive effect from the application of the mastery learning model on students’ learning outcomes on the theme of our friendly environment at class V SD Negeri 097795 Perasmian in the academic year 2022/2023.